2006
DOI: 10.1186/1743-0003-3-17
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of functional weakness and abnormal synergy patterns in the lower limb of individuals with chronic stroke

Abstract: BackgroundThe presence of abnormal muscle activation patterns is a well documented factor limiting the motor rehabilitation of patients following stroke. These abnormal muscle activation patterns, or synergies, have previously been quantified in the upper limbs. Presented here are the lower limb joint torque patterns measured in a standing position of sixteen chronic hemiparetic stroke subjects and sixteen age matched controls used to examine differences in strength and coordination between the two groups.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 23 publications
1
41
0
1
Order By: Relevance
“…Unlike in control participants and the low fall risk group, swing limb GM activity was not significantly associated with FP location. The reduced ability of GM activity to cause more lateral FP may be due to the decreased hip abduction strength of many patients with stroke [43] or an inability to appropriately produce independent GM contractions and isolated frontal plane hip torques [4345]. Within the higher fall risk group, the initial mechanical state of the paretic swing limb also had an altered relationship with its eventual FP location.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in control participants and the low fall risk group, swing limb GM activity was not significantly associated with FP location. The reduced ability of GM activity to cause more lateral FP may be due to the decreased hip abduction strength of many patients with stroke [43] or an inability to appropriately produce independent GM contractions and isolated frontal plane hip torques [4345]. Within the higher fall risk group, the initial mechanical state of the paretic swing limb also had an altered relationship with its eventual FP location.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, those with more severe hemiparesis may not be able to activate the BF, SM, and GM during the tasks, but there is no evidence of mass extension and flexor patterns as the theory behind the FM-LE would assert. In analyses of voluntary single-plane motions while in a functionally significant standing position, Neckel et al 33 demonstrated that while individuals poststroke produce reduced torque in 6 of the 8 motions in the paretic leg, they used similar strategies to controls in 7 of the motions. The only evidence of an abnormal synergy pattern producing the desired movement emerged with maximal hip abduction when hip flexor torque was also recorded in the stereotyped “flexor synergy” activity.…”
Section: Discussionmentioning
confidence: 99%
“…The only evidence of an abnormal synergy pattern producing the desired movement emerged with maximal hip abduction when hip flexor torque was also recorded in the stereotyped “flexor synergy” activity. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies of isometric lower extremity joint-torque coupling in cerebral palsy quantified stereotypical spontaneous coupling between hip and knee extension 20 . However, findings with regards to the expression of abnormal joint coupling patterns on individuals post-stroke have not been conclusive and have not obtained consistent results; some studies demonstrated spontaneous coupling of hip adduction with hip and knee extension torques 17, 20, 21 , coincident with what is described clinically as an “extension synergy” (coupling of hip extension/adduction with knee extension and ankle plantar-flexion 30 ); in contrast, other studies found weakness in specific DOFs but no stereotypical joint torque coupling patterns across subjects 18, 19 .…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, studies were performed in recumbent seating 20 or standing 1719 affecting vestibular and cutaneous input as concluded by Thelen and colleagues 20 . Also, the amount of body weight support provided differed between studies from zero 1, 18, 19 to 100% 17 changing the gravitational contribution to joint torques. Additionally, results could be affected by poorly constrained systems that do not limit movement during maximum torque generation 15, 18, 19 .…”
Section: Introductionmentioning
confidence: 99%